A Case Study On Malaysia National Insurance Berhad - Jofri Rani, Jazira (2006)
This study will briefly describe MNI background and history, organizational structure, competitors and its overall performance throughout its establishment. This case will also highlight MNI's strenght in its management and marketing efforts especially its strategic planning to compete with other Insurance companies globally.